Biomass Pelletizing Machines as a Tool for Waste Valorization and Renewable Energy: A Review Based on an Indigenous Machine Development - O., Oladimeji A.; J., Fawohunre A.; G., Olajide O. (CV. Gio Architect, 2025)
Biomass pelletizing technology is increasingly recognized as a sustainable solution to address global energy demands, waste management challenges, and rural energy poverty. This review presents a comprehensive analysis of biomass pelletizing technology through the lens of a recent research study that involved the design, fabrication, and performance evaluation of an indigenous biomass pelletizing machine in Nigeria. The paper discusses the global relevance of biomass as an energy source, the significance of agricultural waste valorization, the mechanical design principles behind pelletizing equipment, and the technical outcomes of a locally built machine. Key findings revealed an average pelleting capacity of 10.62 kg/hr and an efficiency of 64.8%, with proximate and ultimate analyses supporting the suitability of agricultural waste materials for fuel pellets. The review concludes by affirming the value of biomass pelletizers in fostering sustainable rural development and energy security.